Effects of High Magnetic Field Postannealing on Microstructure and Properties of Pulse Electrodeposited Co-Ni-P Films - Donggang Li; Chun Wu; Qiang Wang; Jean-Paul Chopart; Jicheng He; Agnieszka Franczak; Alexandra Levesque (Advances in Materials Science and Engineering)
The influence of high magnetic field annealing on the morphology, microstructure, and properties of pulsed-electrodeposited Co-Ni-P films was investigated. The as-deposited film with a rough surface changed into uniform nanocrystalline during the magnetic field annealing process. In particular, the formation of intestine-like appearance with spherical clusters vanishing is favored from a moderate magnetic field strength of 6 T, due to the polarized effects. Meantime, the diffraction peak (111) of α (fcc) phase shifts to the right direction, which is attributed to the fact that more Co atoms from phosphide phase are incorporated into the Ni lattice, in comparison with the case of annealing under 0 T and 12 T magnetic fields. The mechanical and magnetic properties of the films reach relative optimum values at B=6 T. The evolution of magneto-induced modification in the Co-Ni-P morphology, structure, and properties can be explained by the polarized effect and the diffusion-acceleration effect under a high magnetic field.